Vitamins E and K: their role and the effects of deficiency - John Knight (Nursing Times, 2024)
This article, the fourth in our series on vitamins and minerals, explores the fat-soluble vitamins E and K. Both vitamins are antioxidants and are primarily obtained from vegetable sources in the diet. Vitamin E is anti-inflammatory and can enhance immune responses, improve glycaemic control and may help protect against cardiovascular and neurological diseases. Vitamin K is a cofactor for an enzyme essential to the formation of clotting factors. Reduced vitamin K has been associated with blood vessel calcification, heart valve calcification and increased risk of coronary artery disease. Newborns and infants are prone to vitamin K deficiency so are given vitamin K injections or oral solutions.